Political communication and election campaigning on instagram during the 14th malaysian general election - Kamaruzzaman Abdul Manan (Tanjung Malim, 2021)
Political communication and election campaigning on instagram during the 14th malaysian general election by Kamaruzzaman Abdul Manan